La ramera bíblica. Lo ‘femenino’ como alegoría estratégica del texto profético - Kirova, Milena (Eslavística Complutense, 2006)
This paper is focusing on an almost obsessive figure of the biblical representation. The harlot, as it happens in many stories, can be a heroine, or a discursive personality, but she can also be an allegorical figure which acts as a signifier of ideas which go far beyond the ‘feminine” problematics. The object of observation here is the second instance, very clearly depicted in the prophetic discourse of the Old Testament. The main texts, upon which I concentrate my observations, are Isaiah, Hosea, Jeremiah and Ezekiel, as well as examples from other prophetic books. The approach is interdiciplinary, in the meeting point of anthropology, Gender Studies, history of Jewish relígio. The main question is: Why should the harlot in the prophetic text of the Old Testament be a woman?